(untitled) (Revista Innova Educación, 2022)
Due to the growing need for scientific publication and having few practical manuals, this article arises. The objective of this document is to guide the process of writing and publishing research results to the scientific community under the IMR&D format (Introduction, Methods, Results and Discussion). This document facilitates research, writing, publication and the elaboration process, both in qualitative and quantitative research, as well as how scientific encryption should be carried out to attract readers. In conclusion, the work aims to make rigorous scientific products viable, through their correct elaboration with guidelines clearly defined by the scientific community.